EXAMINATION OF THE CONDITION OF HARD TISSUES AND DENTAL PULP AFTER THE USE OF CLINICAL WHITENING METHODS - Arziqulova Munisa Shuxratovna (Journals Park Publishing, 2022)
Mentions of the first method of teeth lightening are found in the writings of Guy de Chalice, the personal surgeon of Pope Clement VI and two of his successors - in his treatise Inventories Chirurgical is Medicine. Then the author proposed a bleaching composition based on burnt salt, wine vinegar and honey. For a long time this work remained the main guide for doctors, but with the development of science it gradually lost its relevance.
Keywords: increasing influence; church; chlorides